1999
DOI: 10.1046/j.1365-2222.1999.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of eosinophils and detection of eotaxin in skin chamber fluid after challenge with relevant allergen in patients with mild asthma

Abstract: We have demonstrated a selective recruitment of eosinophils, and higher levels of released ECP and eotaxin, in skin chambers stimulated with allergen, as compared with control chambers. Allergen challenge in skin chambers is a useful tool for studies of eosinophil recruitment, their state of activation, and their involvement in the allergic inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Our results indicate that M.M. 's peripheral blood eosinophils were in a state of activation since there was an increased number of eosinophils and increased expression of the activity markers EG2, CD9, and CD11b ( 2) (compared to reference material from healthy adult subjects analyzed in our laboratory). Suomalainen et al ( 13) found ECP levels to increase after cow's milk provocation.…”
Section: Discussionmentioning
confidence: 58%
“…Our results indicate that M.M. 's peripheral blood eosinophils were in a state of activation since there was an increased number of eosinophils and increased expression of the activity markers EG2, CD9, and CD11b ( 2) (compared to reference material from healthy adult subjects analyzed in our laboratory). Suomalainen et al ( 13) found ECP levels to increase after cow's milk provocation.…”
Section: Discussionmentioning
confidence: 58%
“…For example, the receptor for eotaxin and RANTES, two of the up‐regulated chemokines which we identified, is selectively expressed on human Th2 cells, 32,33 in addition to eosinophils and basophils 34,35 . While the involvement of RANTES in Th2 rather than Th1 type responses is controversial, 36 there is extensive literature on the role of eotaxin in promoting atopic, Th2 responses 37–40 and in the selective recruitment of Th2 cells to the lung in a model of allergic airway disease 41 . As a Th2 cell response is generally thought to be disadvantageous to the control of M. tuberculosis infection, this would suggest that the Mφ response could result in the recruitment of a response which does not favour bacterial elimination.…”
Section: Discussionmentioning
confidence: 92%
“…The in vivo correlation of chemokine expression and eosinophil infiltration has recently been demonstrated (41). Using the skin chamber technique in human atopic subjects, skin blisters were induced after allergen challenge with relevant allergen.…”
Section: The Role Of Chemokines In Allergic Skin Diseasesmentioning
confidence: 99%
“…The number of eosinophils was significantly increased in the allergen‐challenged chambers, and elevated levels of released ECP were found. In the skin chamber fluids, higher peptide levels of eotaxin were detected in the allergen‐challenged individuals than in controls (41). Therefore, eotaxin seems to be of relevance for the recruitment of eosinophils into the skin after allergen challenge in atopic dermatitis (Fig.…”
Section: The Role Of Chemokines In Allergic Skin Diseasesmentioning
confidence: 99%